Microwave Ablation in Primary Lung Malignancies - Moussa, Amgad M.; Ziv, Etay; Solomon, Stephen B.; Camacho, Juan C. (Seminars in Interventional Radiology, 2019)
Lung cancer is the leading cause of cancer-related mortality worldwide. Eighty-five percent of cases correspond to non-small cell lung cancer (NSCLC) and pivotal nonsurgical options for early-stage disease include percutaneous ablation and stereotactic body radiation therapy (SBRT). Microwave Ablation (MWA) is a locoregional treatment option that has many advantages over radiofrequency ablation and has been able to overcome the limitations of this technique in the treatment of early-stage NSCLC. In this review article, we highlight the current evidence supporting the use of MWA in patients with early-stage NSCLC and discuss the technical considerations of the procedure, including optimal patient selection and planning strategies, as well as the potential complications and reported outcomes. Finally, we mention future trends involving ablation in NSCLC, including its role in combination with SBRT in central tumors, management of post-SBRT local recurrence, and its potential as an adjuvant treatment option for patients with resistance to systemic therapy or in combination with checkpoint inhibitors.
Keywords: primary lung tumors; microwave ablation; NSCLC